2016
DOI: 10.1088/1361-6501/28/1/015902
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of porous media flow using hydro-gel beads and LED based PIV

Abstract: A novel experimental approach for measuring porous flow characteristics using spherical hydro-gel beads and particle image velocimetry (PIV) technique is presented. A transparent porous medium consisting of hydro-gel beads that are made of a super-absorbent polymer, allows using water as the fluid phase while simultaneously having the same refractive index. As a result, a more adaptable and cost effective refractive index matched (RIM) medium is created. The transparent nature of the porous medium allows optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…However, they are often difficult to scale-up due to issues related to long-time properties of the suspending solution, thermal stability, handling and cost. Super-absorbent hydrogel particles in water, used in this study, can be advantageously used for performing RIM-PIV as previously shown in Klein et al [13], Byron and Variano [14] and Harshani et al [15]. The mechanical properties of commercially available spherical hydrogel particles are discussed in Dijksman et al [16].…”
Section: Introductionmentioning
confidence: 90%
“…However, they are often difficult to scale-up due to issues related to long-time properties of the suspending solution, thermal stability, handling and cost. Super-absorbent hydrogel particles in water, used in this study, can be advantageously used for performing RIM-PIV as previously shown in Klein et al [13], Byron and Variano [14] and Harshani et al [15]. The mechanical properties of commercially available spherical hydrogel particles are discussed in Dijksman et al [16].…”
Section: Introductionmentioning
confidence: 90%
“…This is due to the difficulties in measuring the flow inside the porous media. The investigations have often used structured porous media, where a laser light sheet can pass through it to illuminate the medium combined with trackable particles following the flow in a standard particle image velocimetry setup [20,21]. Structured porous media, however, cannot provide enough details about flow inside the pores or channeling phenomena that occur due to the interconnectivity of the pores.…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to simplify and reduce the cost of the flow measurement in porous media while achieving RIM, hydrogel beads were used to form the porous media and the medium was illuminated using an LED light source [21]. The longitudinal and transverse velocity fields have been measured and flow channeling has been observed for the interconnected pore paths.…”
Section: Introductionmentioning
confidence: 99%
“…For porous media with regular shaped and sized grains (usually spheres and cylinders), masking has been successfully applied for RIM-coupled PIV (e.g., Hassan and Dominguez-Ontiveros, 2008;Arthur et al, 2009;Satake et al, 2015;Harshani et al, 2017). In these laboratory studies, the authors imposed regular masking shapes onto the images by an a priori approach before conducting the PIV.…”
Section: Introductionmentioning
confidence: 99%